“The Situation is Quite Different.” Perceptions of Violent Conflicts and Training Among German Police Officers - Koerner, Swen; Staller, Mario S. (Frontiers in Education, 2022)
Being a police officer bears the inherent risk of encountering violent conflicts while on duty. Federal reports on violence against German police officers document an increase in registered acts since 2011. However, apart from statistical data, little is known about the qualitative specifics of violent encounters within police operations. At the same time, national and international data point to problems of transfer between training and the field. Against this background, the following study presents the expert views of 29 German Federal police officers which have been interviewed about qualitative specifics of conflict dynamics they had experienced during operations and the extent to which they felt prepared for these situations by means of professional training. Results of the study reveal that violent encounters are perceived as complex, dynamic and ambiguous in nature, in turn demanding high standards of police officers’ awareness, decision-making and interaction skills, ranging from de-escalation to fighting. Moreover, the majority of police officers reported that police training lacked adequate preparation. The findings are discussed through the lenses of professional policing and police training in Germany. For the further empowerment of police organisations, police trainers and police trainer education, we argue that a solid and methodically controlled knowledge base on situational parameters of violent encounters is key.